Ethics of God's Servants Related to The Calls and Duties of Church Service Based on Philippines 2:21-22 - Djone Georges Nicolas (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
This paper aims to analyze the ethics of God's servants related to the calling and duties of church ministry based on Philippians 2:21-21. First, servants of God in carrying out church duties sometimes tend to forget or ignore that they are called and chosen by God to serve souls wholeheartedly and with high ethics. Many servants of God who do not show ethical attitudes that match their status as a servant of God are found so that it becomes a stumbling block within the church as a community of believers, as well as outside the church as an environment that can be reached to Christ. In this paper, the descriptive qualitative method is used, by collecting data through the Bible and other literature books such as journals, interviews, and documents related to the topic of discussion, such as social media and Youtube. As a result, a servant of God is ethically obliged to have the nature of loyalty to God who has called him. Second, a servant of God is ethically obligated to be an example in God's entrusted to service. In conclusion, a servant of God is essentially an ethical human being because he is called by God, the Source of Ethics; the servant of God needs to grasp the essence of his calling by realizing that serving is an honour and grace in God's call. Thus, he is required to show an ethical attitude: a servant of God is ethically obliged to have the nature of loyalty to God who has called him. Second, a servant of God is ethically obliged to be an example in the service God has entrusted to him.